PENDEKATAN TRANSFORMATIVE LEARNING DALAM PENGEMBANGAN PROFESIONALISME GURU [TRANSFORMATIVE LEARNING APPROACH IN TEACHER PROFESSIONAL DEVELOPMENT] - Lo, Sarinah (Polyglot, 2024)
Studies indicate that many teachers who have gone through Teacher Professional Development programs demonstrate no deep change in their educational perspectives and practices. Using a systematic literature review and critical reflection lens, this study aims to provide an alternative for better teacher professional development efficacy. Based on the transformative learning framework, I propose four areas of change that include: the attitude of learning, the approach to learning, the content of learning, and the climate of learning.Bahasa Indonesia Abstrak Penelitian menunjukkan bahwa banyak guru yang mengikuti program pengembangan profesional tidak memberikan perubahan yang mendalam di dalam perspektif dan praktik pendidikan mereka. Menggunakan studi literatur yang sistematik dan refleksi kritis, penelitian ini bertujuan menawarkan alternatif pengembangan professional guru yang lebih baik. Berdasakan kerangka transformative learning, penulis menggusulkan empat area perubahan yang mencakup: sikap belajar, pendekatan pembelajaran, isi pembelajaran, dan iklim pembelajaran.